2021
DOI: 10.1177/02184923211067637
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of povidone iodine for prolonged lung air-leak after lung surgery

Abstract: Background Pulmonary surgery is often associated with postoperative prolonged parenchymal air-leak. The purpose of this study was to determine efficacy and safety of povidone iodine as treatment of prolonged parenchymal air-leak following all-types of lung surgery. Methods This prospective trial was conducted from June 2019 to December 2020, and designed under PanAfrican Clinical Trials Registry requirements. Patients having prolonged parenchymal air-leak were randomly allocated to povidone iodine protocol (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Fever was one of the most common complications, and it must be regarded as a response to the induced inflammation of pleura from chemical sclerosing. Other studies showed that talc pleurodesis yielded up to 31% of fever complications (20), while iodopovidone was associated with fever in 6.1-33% of cases (15,16). Another study comparing talc poudrage with iodopovidone solution by tube thoracostomy showed similar frequencies in terms of fever rates in both groups (21).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fever was one of the most common complications, and it must be regarded as a response to the induced inflammation of pleura from chemical sclerosing. Other studies showed that talc pleurodesis yielded up to 31% of fever complications (20), while iodopovidone was associated with fever in 6.1-33% of cases (15,16). Another study comparing talc poudrage with iodopovidone solution by tube thoracostomy showed similar frequencies in terms of fever rates in both groups (21).…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, several alternatives to talc have been explored in recent years. For example, intrapleural iodopovidone demonstrated its efficacy in recurrent pleural effusion (14) and pneumothorax (15,16). However, there is a lack of studies that firmly assessed the concentration of iodopovidone or specific instructions for its use within the pleural cavity.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, most of literature is about postoperative PAL conservative management, that can rely on fewer options than intraoperative air leak treatment. To date, in case of completely expansible residual lung parenchyma, PAL treatment may be safely attempted by autologous blood patch or chemical pleurodesis (37)(38)(39)(40)(41)(42), whereas in case of residual pleural space, applying suction to the chest drain is still the most effective option available (43)(44)(45)(46)(47)(48). In all cases, digital drainage systems are useful since they allow early patients' mobilization and a real time quantification of air flow (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that Iodine pleurodesis showed favorable results compared with Doxycycline pleurodesis or drainage alone, since POAL and LOS was significantly shorter in the first group, at the cost of slightly increased thoracic pain and few allergic reactions (6%). Also, Chaari and colleagues (42) evaluated the role of Povidone Iodine injection to treat PAL, finding out that after a mean number of 2.11 treatments per patient, drainage period and LOS were significantly shorter if compared to those of untreated patients. In addition, morbidity in the group of untreated patients was more severe, including infections and respiratory distress probably due to persistently incomplete lung re-expansion.…”
Section: Postoperative Pal Conservative Managementmentioning
confidence: 99%
“…Reports of human clinical studies show that povidone-iodine is effective for empyema and pleural infection 3 , 4 . Moreover, pleurodesis using povidone-iodine against air leaks following lung surgery, malignant pleural effusion, and chylothorax has been successful, with the occurrence of only non-serious adverse events such as chest pain 5 7 . However, in Japan, it is currently not approved for use in body cavities because of concerns about tissue damage and residues 8 .…”
Section: Introductionmentioning
confidence: 99%